Colorectal cancer and advanced adenoma incidence during post-polypectomy surveillance: a national cohort study in the English Bowel Cancer Screening Programme - Bonnington, Stewart N.; Hungin, A. Pali S.; Nickerson, Claire; Wright, Suzanne; Sharp, Linda; Rutter, Matthew D. (Endoscopy, 2023)
Background Improved colonoscopy quality has led to debate about whether all post-polypectomy surveillance is justified. We evaluated surveillance within the English Bowel Cancer Screening Programme (BCSP) to determine the yield of surveillance and identify predictive factors for surveillance outcome.Methods We performed a retrospective cohort study of individuals undergoing post-polypectomy surveillance between July 2006 and January 2017. BCSP records were linked to the National Cancer Registration Database to identify interval-type post-colonoscopy colorectal cancers (CRCs). Advanced adenoma and CRC at surveillance were documented. CRC incidence was compared with the general population using standardized incidence ratios (SIRs). Predictors of advanced adenomas at first surveillance (S1), and CRC during follow-up, were identified.Results 44 151 individuals (23 078 intermediate risk; 21 073 high risk) underwent 64 544 surveillance episodes. Advanced adenoma and CRC yields were, respectively, 10.0 % and 0.5 % at S1, 8.5 % and 0.4 % at S2, and 10.8 % and 0.4 % at S3. S1 yield was lowest in those with one index adenoma ≥ 10 mm (advanced adenoma 6.1 %; CRC 0.3 %). The SIR was 0.76 (95 %CI 0.66–0.88), accounted for by the intermediate risk group (intermediate risk SIR 0.61, 95 %CI 0.49–0.75; high risk SIR 0.95, 95 %CI 0.79–1.15). Adenoma multiplicity, presence of a large nonpedunculated adenoma, and greater villous component were associated with advanced adenoma at S1. Older age and multiplicity were significantly associated with CRC risk. Conclusion This large, national analysis found low levels of CRC in those undergoing surveillance and low advanced adenoma yield in most subgroups. Less intensive surveillance in some subgroups is warranted, and surveillance may be avoided in those with a single large adenoma.